The Influence of Tiktok Social Media on Teenagers' Lifestyle (Case Study of UIN North Sumatra Students) - Imamsyah Imamsyah; Mhd Rafli; Musdiansyah Putra; Sugeng Arifandi Banurea; Yudi Bimantaka (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
TikTok is an application that gives each user the freedom to create short videos that can be added with music filters, music and other interesting features. The purpose of this study is to find out how much influence or impact the TikTok application has on the lifestyle of teenagers, especially students at the Islamic state university of north sumatera. As for method using data collection methods such as distributing questionnaires, interviews, documentation and so on depending on which research object is being studied. From the results of the study we found that there was a very large and significant influence caused by this TikTok application. These results can be seen from the test results of the instrument which states that TikTok social media is very influential on the achievement and personality of teenagers.